Implementation of Virtual Reality Museum Lontar Prasi Bali As a Cultural Education Media - Putu Wirayudi Aditama; Christina Purnama Yanti; I Gede Iwan Sudipa (Jurnal Nasional Pendidikan Teknik Informatika : JANAPATI, 2023)
Lontar Prasi Bali is famous for its distinctive paintings on palm leaves, a cultural heritage that must be preserved and continued. Main problem occurred because 82.5% of 189 respondents consisting of elementary school students in Denpasar Selatan stated that they did not know about Lontar Prasi Bali. The aim of collecting data from elementary school student respondents is to increase insight into Lontar Prasi and the target of this research is to introduce VR-based lontar prasi culture to children, especially elementary school students. There needs to be collaboration between culture and technology so that people understand the story and provide education about Lontar Prasi Bali, one of which is by implementing VR. The design method used is MDLC Multimedia Development Life Cycle (MDLC) which consists of concept, design, material collection, assembly, testing and distribution. The results of research using Likert scale stated that the use of VR showed that 84.75% of respondents stated Strongly Agree with the Lontar Prasi Museum Virtual Reality Application.